Identification of lipid specific NKT receptors in the context of Brazil nut allergy - Wang, Rui (2020)
The mechanisms that lead to the development of allergy are still poorly described. In particular what makes an ordinary protein to be recognised as allergen is not yet defined. In order to study the intrinsic allergenicity of proteins, our group has used nut proteins as a model system. The 2S storage albumin from Brazil nut (Ber e 1) in particular is regarded as a major allergen and historically was the first allergen to be transgenically transferred from one plant to another. Whilst Ber e 1 is able to sensitise allergic individuals, the purified protein is not highly immunogenic in animals. Within this project the ongoing hypothesis is that natural lipids present in the nut are required for Ber e 1 to act as an allergen. For this, in the study presented in this PhD dissertation, the main focuses were: (i) to develop in vitro techniques to use stable human cell lines to generate transiently transfected cells for the assessment of natural lipids to act as ligands in the activation of non-conventional T cells; (ii) to identify lipid-binding NKT cells from primary human cultures using a single cell system and NGS with the aim of isolating and characterizing lipid-binding TCR activation; (iii) to express lipid-specific TCRs in surrogate stable human cell lines in order to facilitate a construction of a cell screening lipid library. During this work it was shown that the recombinant TRAV10 protein receptor expressed in Jurkat Lucia cells increased over 72 hours and that CD69 is a better marker for measuring activation in primary NKT cells. Using FACS sorting, primary lipid specific NKT cells from six volunteers (4 allergic and 2 healthy) were successfully isolated from PBMCs and the TCRs sequenced. Over 200 TCR sequences were analysed and nut lipid specific sequences identified. Three pairs of nut lipid-specific-TCR sequences were then cloned into an in house designed acceptor bidirectional plasmid engineered to contain specific type IIS restriction enzymes. Surrogate T cells (Jurkat 76) were subsequently transiently transfected with the nut specific TCRs and co-cultured with human APC presenting lipids. In this system all three transiently transfected T cell lines showed higher IL-2 expression in response to nut lipids than to α-GalCer. The transfected cell lines were used to screen Brazil nut lipid fractions and showed specificity towards phosphatidylethanolamine (PE), phosphatidylserine (PS) and their derivative phospholipids. In the final and exploratory chapter and in order to facilitate the search for new lipid binding-TCRs, a rapid high-throughput methodology for sequencing long-length TCR transcripts using targeted capture and next generation Nanopore sequencing (MinION) was described. Human PBMCs from a healthy volunteer were isolated and co-cultured with APCs in the presence of six different lipids before RNA isolation. A total of 40,862 transcripts were obtained in the first MinION run, which uniquely aligned to TCR constant regions. Initial analyses involving only TCR alpha chains have shown that 3 were specific to α-GalCer, 13 to Sulfatide, 4 to Lactosylceramides, 27 to Brazil nut lipid, 29 to Lipopolysaccharides (LPS) and 3 to Lyso-phosphatidylethanolamine (LPE). The full bioinformatic processing of the remaining data is ongoing. The results shown here therefore further suggest that particular classes of nut lipids are involved in the activation of NKT cells from nut allergic patients and that α/β and / TCR receptors are involved in the mechanisms of activation. The results from this study will help to characterise the intrinsic factors linked to Ber e 1 allergenicity and ultimately will help to define what makes a common protein, within a food matrix context, to function as an allergen to a group of susceptible individuals. The surrogate systems presented here are important first steps in the establishment of human cell-specific lipid responsive libraries for the study of natural lipid substances.